Kajian Yuridis Terhadap Pengaturan Platform Jasa Kesehatan Online Sesuai Dengan Ketentuan Kementerian Kesehatan - Ni Kadek Derlin Yanti; Anak Agung Sagung Laksmi Dewi; Ni Made Sukaryati Karma (Jurnal Analogi Hukum, 2025)
Advances in Information and communication technology have transformed the world into one borderless sphere. Online health platform is one form of change in the health sector that utilizes technology to provide health services by doctors to patients online. The problem in this study is (1) How the regulation of online health service platforms in accordance with the Ministry of Health? And (2) How  sanctions for medical personnel who do not meet the standards of the Ministry of Health?. The research method used includes normative legal research through statutory and conceptual approaches. The legal regulation of online health services is regulated in Law 36 of 2009 concerning Health as part of the provision of health services, ITE Law Number 11 of 2008 which regulates the operation of electronic systems and Permenkes Number 20 of 2019 which further regulates the implementation of telemedicine. Patients who are harmed can file for liability by submitting a complaint to the Indonesian Medical Discipline Honor Council. The decision (MKDKI) can be binding on doctors, dentists, and KKI who can hand out not guilty decisions or give punishments following the provisions in Article 69 of the Medical Practice Act.